2022
DOI: 10.47197/retos.v46.94080
|View full text |Cite
|
Sign up to set email alerts
|

The development of reflective skills in physical education teacher education: a systematic review

Abstract: Research has shown an increased attention towards Reflective Practice as a successful aspect in the professional development of Physical Education Teacher Education. Notwithstanding, there is a lack of empirical research about how teachers’ reflective skills should be developed in this context. The aim of this systematic review was to understand what and how has been studied about physical education teachers’ reflective skills, and how such strategies can be further developed and refined in Physical Education … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 76 publications
(286 reference statements)
0
4
0
Order By: Relevance
“…Nevertheless, the reflective practice process presents challenges and complexities that hinder inexperienced teachers from fully engaging in this transformative process. Consequently, when asked to reflect on their teaching-learning experiences, PSTs tend to provide summaries with descriptive rather than analytical insights [10,11]. This challenge primarily arises from their tendency to prioritize content knowledge in teaching-learning practice [12], resulting in a surface-level understanding of reflection as a routine task in their profession, lacking in-depth interpretation [13].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the reflective practice process presents challenges and complexities that hinder inexperienced teachers from fully engaging in this transformative process. Consequently, when asked to reflect on their teaching-learning experiences, PSTs tend to provide summaries with descriptive rather than analytical insights [10,11]. This challenge primarily arises from their tendency to prioritize content knowledge in teaching-learning practice [12], resulting in a surface-level understanding of reflection as a routine task in their profession, lacking in-depth interpretation [13].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, written reflection combined with peer observation not only increases self-awareness (Korucu Kis & Kartal, 2019), but also the focus and complexity of PSTs' reflections (McCormack, 2001). Research in PE has been highlighted reflective writing and peer observation as predominant strategies to promote PSTs' reflection (Azevedo et al, 2022). However to our knowledge, there have been no studies that have examined, in a complementary fashion, the combination of peer observation and written reflection pedagogical strategies to develop the temporal dynamics of reflection in PST.…”
Section: Introductionmentioning
confidence: 99%
“…Prior research in physical education teacher education (PETE) programs has shown that PSTs often focus on describing classroom practices (Standal and Moe, 2013;Zhu, 2011) and tend to replicate established ideas (Greve et al, 2021). Therefore, despite its recognized importance in fostering deep thinking through self-questioning, contextual analysis, and consideration of others in the teaching-learning practice, critical reflection has been challenging to develop among PSTs (Azevedo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…One crucial step in developing critical reflection among PSTs is learning to question their teaching decisions (Turan and Koç, 2019). However, the development of critical reflection among PSTs has often been overlooked in PETE contexts because of the traditional use of the dualistic approach 2 (Azevedo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%